Efficacy and safety of stereotactic body radiotherapy (SBRT) in oligometastatic/persistent/recurrent ovarian cancer: a prospective, multicenter phase II study (MITO-RT3/RAD). Issue 7 (21st June 2021) - Macchia, Gabriella; Jereczek-Fossa, Barbara Alicja; Lazzari, Roberta; Cerrotta, Annamaria; Deodato, Francesco; Ippolito, Edy; Aristei, Cynthia; Gambacorta, Maria Antonietta; Scambia, Giovanni; Valentini, Vincenzo; Ferrandina, Gabriella
Abstract : Background: Stereotactic body radiotherapy (SBRT) has shown promising results in the clinical setting of oligometastatic, persistent, or recurrent disease in several malignancies including ovarian cancer. Primary Objective: The MITO-RT3/RAD trial is a prospective, multicenter phase II study aimed at identifying potential predictors of response and clinical outcome after SBRT treatment. Study Hypothesis: Radiotherapy delivered by pre-defined SBRT treatment schedules and shared constraints could improve the rate of complete response. Trial Design: All patients accrued will be treated with a radiotherapy dose in the range of 30–50 Gy by 1, 3, or 5 SBRT daily fractions to all sites of active metastatic disease according to diagnostic imaging. Schedules of treatment and dose prescription have been established before considering target sites and healthy organ dose constraints. Follow-up and monitoring of side effects will be carried out every 3 months for the first year with imaging and clinical evalutation, and every 4 months within the second year; thereafter, surveillance will be carried out every 6 months. The best response on a per lesion basis will be evaluated by computed tomographic (CT) scan, positron emission tomography/CT, or magnetic resonance imaging in case of brain lesions, every 3 months. Major Inclusion/Exclusion Criteria: The study includes patients with oligometastatic, persistent, or recurrent ovarian cancer for which salvage surgery or other local therapies are not feasible due to any relative contra-indication to further systemic therapy because of serious co-morbidities, previous severe toxicity, unavailability of potentially active systemic therapy, or patient refusal. Primary Endpoint: The primary endpoint of the study is the clinical complete response rate to SBRT by imaging on a per lesion basis. Sample Size: Approximately 205 lesions will be treated (90 lymph nodes and 115 parenchyma lesions). Estimated Dates for Completing Accrual and Presenting Results: Fifty-two centers have expressed their intention to participate. Enrollment should be completed by March 2023 and analysis will be completed in September 2023. Trial Registration: NCT04593381 .